Stress Analysis of the Flexspline with Double- circular- arc Tooth Profile and Variable Structure - Zhang Yushuang; Wang Jiaxu; Wang Zhengwei; Pu Wei; Li Junyang; Zhou Guangwu (Jixie chuandong)
The overall three- dimensional assembly models of harmonic gear drive with double- circular- arc tooth profile and elliptical wave generator is established,then,the finite element analysis of the assembly model is carried out. Some improvements of the flexspline structure including fillet radius on flexible gear tooth and cut on smooth cylindrical outer surface of the flexible wheel is carried out on the basic structure,on The stress distribution and stress concentration of the flexspline are compared and analyzed. And the variation condition of the flexspline stress with the size of gear tooth fillet radius and the cut into the depth of arc of e flexible wheel smooth cylindrical outer surface is analyzed.